Sozophytes (red-listed species) in Silesian anthropogenic habitats and their role in nature conservation - Nowak, Arkadiusz (Biodiversity: Research and Conservation, 2006)
Floristic research was conducted in anthropogenic habitats in Silesia in 1997-2005 and it focused on occurrence of red-listed taxa in habitats strongly transformed by man. As a result of the study, 362 sozophyte species of various threat categories were found in man-made biotopes. An analysis of frequency classes of occurrence in anthropogenic habitats in relation to the total number of sites of a given species revealed that almost 100 sozophyte taxa have over 66% of their locations in anthropogenic habitats. The study confirmed that anthropogenic habitats can serve as the last refuges for many threatened species, which are extinct in natural or semi-natural habitats. The investigations show that man-made habitats could shift the range limits of threatened species and support their dispersal. Out of the 362 analysed species, 164 were recognised to occur in other than typical plant communities. Man-made habitats create particular environmental conditions for development of specific plant communities, which are not found in natural biotopes in surrounding areas or even not described before. Thus the habitats strongly transformed by man are important for protection of the natural floristic diversity and must not be omitted in strategies of nature conservation.